A THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT ON CAREER SATISFACTION AMONG REMOTE WORKER: PARALLEL MEDIATION OF DIGITAL SELF-EFFICACY AND PERCEIVED EMPLOYABILITY - Tika Rahma Yani Siregar; Ratu Aisyah Ratih Primaputri; Muhammad Ridho Sahputra (TECHNOBIZ : International Journal of Business, 2025)
This study investigates the impact of perceived organizational support on career satisfaction among remote workers . It also explores the mediating effect of perceived employability and digital self-efficacy in this relationship. Using a multi-item survey questionnaire, 210 remote workers from Hajj Umrah travel company in West Sumatra, Indonesia were assessed. To test the hypotheses, a quantitative approach incorporating structural equation modelling (SEM) was used using SmartPLS 4.0. To examine the mediating effects of perceived employability and digital self-efficacy on the association between perceived organizational support and career satisfaction, the bootstrapping technique was performed. We found positive and significant association between perceived organizational support and career satisfaction. Additionally, we found evidence of parallel mediation, where digital self-efficacy and perceived employability mediate the relationship between perceived organizational support and career satisfaction. This study extends the existing literature by exploring career satisfaction in career management.